Height increment of Cycas micronesica informs conservation decisions. (1st December 2020) - Marler, Thomas E.; Griffith, M. Patrick; Krishnapillai, Murukesan V.
ABSTRACT: Growth dynamics of pachycaulous stems of arborescent cycad plants are not well understood, and most observations have been made in cultivated garden plants. We studied Cycas micronesica plants in Guam, Tinian, and Yap to understand the influences of geography, plant size, sex, and herbivory on stem growth. We also determined the changes in demography of Guam's population after 15 years of damage by non-native insect herbivores. The height increment (HI) was similar for plants within the height range from 100 cm to more than 600 cm, so the relative growth rate declined with height. Female tree HI was 68% of male tree HI, and Yap tree HI was 87% of Guam tree HI. Chronic herbivory by non-native insect herbivores caused a mean 44% decline in HI. Plants in managed gardens grew more rapidly than plants in a wild habitat. The HI was used to estimate that Guam has experienced a complete loss of ≈70 y of demographic depth resulting from the selective mortality of small plants since 2005. When future conservation interventions successfully mitigate the ubiquitous biological threats, our HI may be useful for empirically quantifying recovery of plant health.